2011
DOI: 10.3171/2010.3.jns10144
|View full text |Cite
|
Sign up to set email alerts
|

Neural interconnections between the nerves of the upper limb and surgical implications

Abstract: The knowledge of neural interconnections between adjacent nerves of the upper limb is important to the surgeon as such variations may lead to issues with surgical identification and thus iatrogenic injury. Trauma or entrapment of these nerves may cause functional losses different from those expected and thus result in misdiagnosis. The authors review the literature regarding such nervous system derangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
0
19
0
2
Order By: Relevance
“…A total of 6 studies ( n = 501 hands) reported the prevalence of RCA . The overall pooled prevalence of RCA was 55.5% (95% CI, 30.6%–79.1%; Cochran Q, P < 0.001; I‐squared = 96.0%, 95% CI, 93.4%–97.5%) (Table ; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 6 studies ( n = 501 hands) reported the prevalence of RCA . The overall pooled prevalence of RCA was 55.5% (95% CI, 30.6%–79.1%; Cochran Q, P < 0.001; I‐squared = 96.0%, 95% CI, 93.4%–97.5%) (Table ; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A further genetic link was demonstrated by Srinivasan and Rhodes who demonstrated that fetuses with congenital defects, particularly Trisomy 21, presented with MGA bilaterally. The MGA has mainly been reported to supply motor innervation to the thenar, hypothenar, and dorsal interosseous muscles; however, some sensory fibers have also been identified …”
mentioning
confidence: 99%
“…Although it is rare, the isolated lesion of the MCN (iatrogenic or traumatic) located proximal with respect to an anastomosis of this type, would have as a consequence the paresis of the flexion of the extrinsic muscles of the hand, associated with the plejia of the flexion Of elbow. This must be taken into account not only in the scenario of traumatic injuries of the MCN, but in its possible application in the anesthetic blocks of peripheral nerves [14]. Finally, given the patients who suffer a brachial plexus lesion may have variable distribution patterns, the intra-operative neurophysiological finding clearly leads us to the topographic approach.…”
Section: Discussionmentioning
confidence: 99%
“…The ulnar nerve has a dorsal branch that arises proximal to the wrist, passes distally and dorsally, deep to the flexor carpi ulnaris, and perforates the deep fascia to descend along the medial side of the wrist and hand to divide into two or three dorsal digital nerves (Loukas et al, 2007). This communication comes by way of the fifth dorsal digital branch of the radial nerve, supplying the adjoining sides of the third and fourth digits and is often replaced by a dorsal branch of the ulnar nerve (Drake et al, 2005;Standring et al, 2008;Loukas et al, 2010). In this study, a deep communicating branch was found in 16% of the dissected specimens.…”
Section: Discussionmentioning
confidence: 99%